Survey data on livelihood assets, activities and outcomes of smallholder farm households in China's Loess Plateau - Qirui Li (Elsevier, 2021)
Smallholders’ decisions on land use and their activities and strategies of livelihoods are the critical source of uncertainty in natural resource use and an essential determinant of sustainability challenges. This data article provides a selection of quantitative data from a questionnaire survey on livelihood assets, activities and outcomes of smallholder farm households in Yan'he Township, which lies in the middle part of China's Loess Plateau, one of the representative Grain for Green Project areas [1]. Data include land-use decisions and agronomic practices, fertilisation, use of pesticides, machine and irrigation, farm and non-farm activities, financial performance, and the levels of household income, wellness, and total consumption of food, energy, and education and health care. The survey also covered geographical, demographic and socioeconomic background information on the respondents and their perceptions, incentives, propensities and subjective wellbeing. The survey has supported a couple of research articles that build indicators and indexes for economic, environmental and socio-cultural sustainability dimensions and the resilience building of coupled social-ecological systems. The data presented in this article were analysed using descriptive and inferential statistics and provided at the Mendeley Repository. The data will assist studies on the interrelationships of smallholder livelihoods, ecosystem conservation, interventionist policy and market support, and community capacity building in sustainability science.